NILAI-NILAI PENDIDIKAN DALAM KITAB SIRAJ AL THALIBIN KARYA SYEKH IHSAN BIN DAHLAN - Fatkhul Wahab (Jurnal Studi Pesantren, 2023)
Education aims to (1) develop morally good and correct behavior, (2) cultivate autonomous reflection skills, (3) internalize moral values and norms in facing concrete life situations, (4) adopt universal principles and life values as a foundation for moral development in decision-making, and (5) make righteous, moral, and wise decisions. The purpose of this research is to understand the concept of education contained in the book "Siraj Al Thalibin". This research is a library research. The research type is qualitative descriptive using the Content Analysis method. The data sources include: (a) Primary sources, namely the book "Siraj Al Thalibin" by Sheikh Ihsan Bin Sheikh Dahlan. (b) Secondary data sources include journals, relevant books, etc. The results of this study indicate that Islamic education is not merely theoretical but must be applied in daily life. Among them are: (1) the habit of reciting basmalah and hamdalah, (2) the importance of seeking knowledge, (3) emulating the beloved of Allah SWT, (4) constantly remembering Allah SWT, (5) performing worship properly, (6) refraining from indulging in desires, (7) obedience, reliance, patience, contentment, and sincerity, and (8) constantly repenting to Allah SWT. Keywords: Educational Value, Kitab Siraj Al Thalibin